Insulin-Enhanced Biological Visual Rehabilitation in Neuroretinal Degeneration Patients Treated with Mesenchymal Cell-Derived Secretome - Paolo Giuseppe Limoli; Celeste Limoli; Marcella Nebbioso (Pharmaceutics)
Objectives: Insulin plays a crucial role in neuronal survival and oxidative stress modulation, making it a potential therapeutic target. This study investigates the effects of insulin in combination with a mesenchymal cell-derived secretome in patients with degenerative neuroretinal diseases. Methods: Sixty-four patients with severe neuroretinal diseases who had previously undergone the Limoli Retinal Restoration Technique (LRRT) were included in this longitudinal study and divided into groups: group 1 received a single injection of 5 units of insulin lispro into the suprachoroidal space of the worse-seeing eye; group 2 received insulin injection in the better-seeing eye. Retinal function was assessed using microperimetry (MY) before and after treatment (approximately 1 year for eye drops). Group 3 consisted of patients who demonstrated improvement in MY after insulin injection. These patients continued treatment with daily insulin eye drops. Results: In group 1, insulin-treated eyes showed a significant increase in retinal sensitivity from 10.09 dB to 10.75 dB (p = 0.0067), while untreated eyes declined from 12.35 dB to 11.92 dB (p = 0.0448). In group 2, insulin-treated eyes improved from 10.8 dB to 11.63 dB (p = 0.05), whereas untreated eyes exhibited a decline from 8.68 dB to 8.50 dB (p = 0.6771). In group 3, patients using insulin eye drops showed a stabilization or mild increase in retinal sensitivity, from 11.39 dB to 11.73 dB (p = 0.231). Conclusions: The addition of insulin in patients previously treated with the LRRT was associated with improved sensitivity and a stabilizing effect on neuroretinal function.